Workshop Pengembangan Kepemimpinan Strategis dalam Meningkatkan Mutu Pendidikan di Lingkungan Yayasan Pondok Pesantren Al Mawaddah Warrahmah Kolaka - Sulkifli Ar; Musdalifah Musdalifah; Suhrah Suhrah; Muthahharah Idris; Rina Nur Afifa; A. Husnul Khatimah; Rahmi Rahmi (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
Strategic leadership is a key factor in improving the quality of education, particularly within Islamic boarding school (pesantren) institutions that are characterized by unique values and organizational cultures. This community service activity aimed to enhance the strategic leadership competencies of school principals and prospective vice principals under the auspices of the Al Mawaddah Warrahmah Islamic Boarding School Foundation in Kolaka. The method used was a participatory approach through interactive, andragogy-based training strategies, including lectures, case studies, group discussions, role-play simulations, and the development of follow-up action plans (RTL). The results of the workshop indicated significant improvements in participants’ cognitive, affective, and psychomotor domains, as evidenced by increased post-test scores, improved capacity in strategic planning, and the establishment of a collaborative leadership forum among educational leaders. Furthermore, the activity fostered a renewed awareness of the importance of transformational and values-based leadership in managing Islamic educational institutions. It is recommended that similar training be conducted regularly with structured mentoring and performance-based evaluation systems. Thus, this workshop made a tangible contribution to strengthening strategic, collaborative, and quality-oriented educational governance in the pesantren environment.